(untitled) (Vietnam Journal of Community Medicine, 2026)
1) Objectives: To determine the prevalence of depression and its associations with social support and treatment adherence among HIV-positive men who have sex with men (MSM) at outpatient clinics in Ho Chi Minh City. 2) Methods: A cross-sectional study on 412 MSM patients receiving ARV treatment at three ward health stations: Xom Chieu, Cho Lon, and Phu Tho Hoa. Chi-square () and Fisher’s exact tests were utilized to determine the relationships between independent variables and depression status. 3) Results: The prevalence of depression was 16.3%. The treatment adherence rate was very high at 93.9%, and the majority of patients reported high (43.0%) and moderate (35.9%) levels of social support. The study found statistically significant associations between depression and both treatment adherence (p = 0.033) and the level of social support (p = 0.036). Additionally, income and sexual behavior characteristics were also related to depression (p < 0.05). 4) Conclusions: In univariate analysis, depression in MSM was significantly correlated with social support and treatment adherence. It is necessary to strengthen social support networks and psychological interventions to optimize ARV treatment efficacy.